The roles of sleep and executive function in adolescent nighttime eating. (August 2022) - Tomaso, Cara C.; Yaroch, Amy L.; Hill, Jennie L.; Jackson, Tammy; Nelson, Jennifer M.; James, Tiffany; Mason, W. Alex; Espy, Kimberly A.; Nelson, Timothy D.
Abstract: Nighttime eating has been associated with obesity, inflammation, and poor nutritional intake, yet correlates of this behavior are understudied in pediatric populations and among adolescents in particular. The current study examines modifiable factors related to nighttime eating, including sleep parameters and regulatory abilities—as well as the interplay between these constructs—in adolescents. A total of 223 adolescents ( M age  = 15.32 years, 52.9 % female, 15.7 % classified as overweight, 21.1 % had obesity) wore ActiGraph devices to measure sleep and were instructed to complete three 24-h dietary recall measures over a two-week period. Participants also completed self-report measures of executive function. Greater variability in sleep duration was consistently associated with higher average calorie, sugar, and fat consumption after 8, 9, and 10 PM. The main effect of global executive function on all nighttime eating measures was nonsignificant, and executive function did not moderate relationships between sleep parameters and nighttime eating measures. Since adolescents' eating habits may set the stage for lifelong dietary practices, efforts to ensure consistent sleep duration may reduce risk for nighttime eating in this nutritionally vulnerable population. Highlights: Nighttime eating is a potentially obesogenic behavior. Correlates of nighttime eating are not well-studied in pediatric samples. Regulatory abilities were not associated with nighttime eating measures. Greater sleep time variability was related to nighttime eating. Targeting sleep time consistency could be important for curbing nighttime eating.